The change ebook - Goldberg, Whoopi (The Change., 2024)
Whoopi Goldberg brings new meaning to what it means to be a superhero in a new graphic novel!Isabel Frost is a woman who has spent her life as wife, mother, grandmother—a life she feels isn't all she had hoped for, with a husband who has grown in another direction. With a background in computer science, Isabel is an amazing gamer who plays with people all over the country. With the help of her comic-loving grandson and irreverent best friend, she must learn to control her abilities and embrace her new identity as The Change—both the change of life AND her surprising and extraordinary superpowers.